Mutual Authentication In Ip Mobility-Enabled Multihop Wireless Networks" Security For Multihop Wireless Networks (2014)
An important requirement for current mobile Wireless networks, such as vehicular ad hoc networks (VANETs), is their ability to provide ubiquitous and seamless IP communications in a secure way. Moreover, these networks are envisioned to support multihop communications, in which intermediate nodes help relay packets between two peers in the network. The combination of the two capabilities, namely, the seamless support of IP communications and multihop communications, is denominated IP mobility-enabled multihop wireless networks.